PENYULUHAN PEMANFAATAN LIMBAH USUS AYAM MENJADI POC DAN DAMPAKNYA PADA PENGETAHUAN IBU RUMAH TANGGA - Islawati Islawati; Sugiarti Sugiarti; Suhartini Azis; Buya Hamka; Yati Bt Samsuddin (SEBA: Jurnal Pengabdian kepada Masyarakat, 2026)
Improper disposal of chicken intestines waste in Batu Mila Village may generate environmental nuisance and public health risks due to unmanaged dumping practices. This community service program aimed to increase housewives’ knowledge and stimulate initial readiness for behavioral change regarding the potential utilization of chicken intestines/offal waste as a raw material for liquid organic fertilizer (LOF) through a circular economy approach. The program was delivered as an educational outreach session (counseling), not a hands-on training, and was evaluated using a one-group pretest–posttest design. Knowledge was measured with a 20-item multiple-choice instrument scored on a 0–100 scale. The results indicated a substantial improvement in mean knowledge scores from 55.3 (pretest) to 86.73 (posttest), with an N-Gain of 0.731, demonstrating high effectiveness of the outreach in strengthening participants’ understanding. These findings highlight that circular economy-based counseling can function as an important pre-adoption stage to build cognitive foundations and psychosocial readiness to reduce unsafe disposal practices and consider resource recovery options for chicken intestines/offal waste. In conclusion, the outreach effectively improved knowledge as a prerequisite for behavioral change; follow-up reinforcement and medium-term evaluation are recommended to assess knowledge retention and more stable behavioral indicators. Keywords: counseling; circular economy; chicken intestines waste; liquid organic fertilizer; pretest–posttest